Control of ochratoxin A-producing fungi in grape berry by microbial antagonists: A review. (May 2016) - Zhang, Hongyin; Apaliya, Maurice Tibiru; Mahunu, Gustav K.; Chen, Liangliang; Li, Wanhai
Abstract: Background: Ochratoxin A (OTA) remains a challenge in the face of continuous efforts to produce quality and wholesome wine and table grape berries to meet food safety standards. However, the use of chemicals to control postharvest diseases is a public concern with increasing consumer awareness of the dangers associated with the consumption of fungicide-treated commodities. Synthetic fungicides are well-known for their hazardous effects on human health and potential contamination to the environment. Moreover, pathogens are noted to have developed resistance to these chemicals because of their continuous use and abuse. Scope and approach: This review focused on the efficacies, potentials and developmental trends of microbial antagonists in the control and biodegradation of OTA-producing fungi in grapes and wine. It outlined the steps and challenges in the development of bioproducts. It also recounted the successes and developments of biocontrol products to date. Key findings and conclusions: OTA production in grapes is caused by the genera Aspergillus and Penicillium, with the species Aspergillus carbanarius as the dominant cause across the globe. The prevalence of OTA-producing fungi in grape vineyards are influenced by temperature, water activity (aw ), pH, relative humidity and type of cultivar. Biological control agents (BCAs) have proved successful to control and/or degrade OTA-producing fungi, among which antagonistic yeasts play the leading role. In addition, biocontrol products such as BioSave, Yieldplus, Serenade and Aspire have been developed. Preharvest application is acknowledged to be the best for grapes even a day before harvest because postharvest treatment affects the bloom of the grapes. Highlights: Biological control agents have proved successful to control OTA-producing fungi. Mechanisms of action of BCAs against OTA-producing fungi are reviewed. Environmental conditions and location affect the growth of OTA-producing fungi. Preharvest applications of BCAs are promising means to reduce OTA-producing fungi.